PENDIDIKAN DAMAI (PEACE EDUCATION) BAGI ANAK-ANAK KORBAN KONFLIK - Sukendar, Sukendar (WALISONGO, 2011)
Abstract Â  The conflict is as natural of law (sunnatullah) that always there in the course of human life. So that conflicts do not lead to violence and social disaster, the conflicts need to be managed properly. Managing conflicts is not solely aimed at the cessation of conflict, or the signing of a peace agreement between the parties to the dispute. Over, conflict management must be followed by the management of post-conflict conditions. Among the efforts the condition of post-conflict is recovery of the affected populations, especially children who are the most vulnerable groups in a conflict. One remedy is to educate children affected by conflict through peace education. This needs to be done so that they are free from the trauma, did not carry a grudge in life, and capable of being a man who loves peace. This study will explore the efforts of peace education for children affected by conflict in the Latansa Islamic Boarding School, Cangkring, Karanganyar, Demak. *** Â  Konflik merupakan sesuatu yang alami yang selalu ada dalam kehidupan manusia. Oleh karena itu agar konflik tidak mengakibatkan kekerasan dan petaka sosial maka konflik perlu dikelola dengan tepat. Mengelola konflik tidak sematamata ditujukan bagi penghentian konflik atau penandatanganan kesepakatan antara kelompok-kelompok yang bertikai. Lebih dari itu, manajemen konflik harus diikuti dengan manajemen post-konflik. Di antara berbagai upaya manajemen post-konflik adalah pemulihan terhadap orang-orang yang menjadi korban konflik, khususnya anak-anak yang memang rentan terhadap efek konflik. Salah satu penanganannya adalah melalui pendidikan agar mereka terbebas dari perasaan traumatik, tidak membawa kedukaan mereka, serta mampu menjadi orang yang mencintai perdamaian. Kajian ini akan melihat bagaimana upaya pendidikan damai yang dilakukan oleh Pondok Pesantren Latansa Cangkring Karanganyar Demak. Keywords: pendidikan damai, korban, konflik